2022
DOI: 10.1038/s41420-022-01162-7
|View full text |Cite
|
Sign up to set email alerts
|

RING-finger E3 ligases regulatory network in PI3K/AKT-mediated glucose metabolism

Abstract: The phosphatidylinositol 3-kinase (PI3K)/AKT signaling pathway plays an essential role in glucose metabolism, promoting glycolysis and resisting gluconeogenesis. PI3K/AKT signaling can directly alter glucose metabolism by phosphorylating several metabolic enzymes or regulators of nutrient transport. It can indirectly promote sustained aerobic glycolysis by increasing glucose transporters and glycolytic enzymes, which are mediated by downstream transcription factors. E3 ubiquitin ligase RING-finger proteins are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 116 publications
1
15
0
Order By: Relevance
“…Downstream signals of PI3K are mediated by multiple serine/threonine (Ser/Thr) kinases, including phosphoinositide-dependent protein kinase 1 (PDK1), AKT, mammalian target of rapamycin complex (mTORC), protein kinase C (PKC), ribosomal protein S6 kinase (S6K), AKT substrate of 160 kDa (AS160) and glycogen synthase kinase 3 (GSK3), which regulate the activity of various transcriptional factors, such as Forkhead box protein O1 (FOXO1), peroxisome proliferator-activated receptors (PPARs), PPARγ coactivator-1 alpha (PGC1α), and sterol regulatory element-binding proteins (SREBPs). These promote the metabolic actions of insulin on glucose, lipid, and mitochondrial metabolism, as well as effects on cell proliferation, differentiation, growth and apoptosis [30][31][32][33][34][35][36][37].…”
Section: Distinct Function Of the Pi3k/akt Signaling Pathway In Diffe...mentioning
confidence: 99%
See 1 more Smart Citation
“…Downstream signals of PI3K are mediated by multiple serine/threonine (Ser/Thr) kinases, including phosphoinositide-dependent protein kinase 1 (PDK1), AKT, mammalian target of rapamycin complex (mTORC), protein kinase C (PKC), ribosomal protein S6 kinase (S6K), AKT substrate of 160 kDa (AS160) and glycogen synthase kinase 3 (GSK3), which regulate the activity of various transcriptional factors, such as Forkhead box protein O1 (FOXO1), peroxisome proliferator-activated receptors (PPARs), PPARγ coactivator-1 alpha (PGC1α), and sterol regulatory element-binding proteins (SREBPs). These promote the metabolic actions of insulin on glucose, lipid, and mitochondrial metabolism, as well as effects on cell proliferation, differentiation, growth and apoptosis [30][31][32][33][34][35][36][37].…”
Section: Distinct Function Of the Pi3k/akt Signaling Pathway In Diffe...mentioning
confidence: 99%
“…Another concern is that PI3K/AKT signaling mediates a wide spectrum of processes in the whole organism (special attention should be paid to oncogenesis), which additionally complicates development of an anti-obesity therapy that specifically targets at its modulation [26,33,36]. Finally, selective interaction with tissue specific isoforms of both PI3K and AKT could probably ensure tissue specific response [140].…”
Section: Future Perspectives For Translation Of Natural Pi3k/akt Modu...mentioning
confidence: 99%
“…We showed that ARID3A In our study, we found that PI3K inhibition blocked the stimulatory effect of PA on ARID3A protein expression. The PI3K signaling is one of the most important intracellular signaling sensing nutrients to regulate multiple cellular functions, including cell proliferation, differentiation, and expression of many genes (Tsalikis et al, 2013;Wang et al, 2022). Fatty acids can promote milk fat synthesis in mammary epithelial cells through the PI3K signaling (Jin et al, 2022;F.…”
Section: Arid3a Mediates Pa Stimulation On Srebp1 Mrna Expressionmentioning
confidence: 99%
“…Cellular signaling pathways are an intricate ballet of interacting proteins involved in transmitting signals from extracellular to intracellular regions 7,8 . Notably, emerging research has markedly improved our understanding of PI3K/Akt‐associated signaling pathways in MS 9–12 . Cellular receptors, secondary molecules/messengers, and transcriptional factors are imperative elements for signaling pathways 8 .…”
Section: Introductionmentioning
confidence: 99%